Functional biogeography of marine vertebrates in Atlantic Ocean reefs. (29th October 2021) - Waechter, Luiza S.; Luiz, Osmar J.; Leprieur, Fabien; Bender, Mariana G.
Abstract: Aim: Marine vertebrates play key functional roles on reef ecosystems. Despite their phylogenetic distance, different vertebrate lineages could play similar functions on reefs, which has been overlooked by current research on marine functional biogeography. We provide the first comprehensive assessment of the functional structure and inventory of ecosystem functions delivered by 224 vertebrates—marine mammals, sea turtles, sharks, rays and bony fish—in Atlantic Ocean reefs. Location: Atlantic Ocean reefs. Methods: We compiled six species‐level traits and investigated geographical patterns of functional richness (FRic), functional uniqueness (FUn) and specialization (FSpe) in 83 assemblages. Additionally, we simulate the effects of marine vertebrate species' extinction on functional diversity metrics. Results: Sharks, rays and bony fish species had the highest overlap in functional space (30.94%), while turtles overlapped mainly with bony fishes (1.76%). The functional structure of vertebrate assemblages is not homogeneous across the Atlantic. While functional richness peaks in the Caribbean (a " functional hotspot" ), this region depicts low‐to‐intermediate functional uniqueness and functional specialization levels. Despite the large proportion of threatened top predator species (53.1%), mainly large‐bodied sharks, it is the loss of mesopredator species that will severely impact (up to 94% of functional loss) the functional space of vertebrate assemblages in Atlantic Ocean reefs. Main conclusions: Our study reveals that functional richness patterns of vertebrate assemblages differ across Atlantic Ocean reefs. Despite the low values of functional uniqueness and specialization in some reef assemblages, reef functioning can still be compromised due to species' extinctions. The impact of mesopredators' loss over the functional structure of vertebrate assemblages is worrisome since this group holds a considerable proportion of threatened species (20.1%) and is next in line considering the anthropogenic impacts over high trophic level species.